2016
DOI: 10.1016/j.chemosphere.2016.03.097
|View full text |Cite
|
Sign up to set email alerts
|

Introducing sequential managed aquifer recharge technology (SMART) – From laboratory to full-scale application

Abstract: Previous lab-scale studies demonstrated that stimulating the indigenous soil microbial community of groundwater recharge systems by manipulating the availability of biodegradable organic carbon (BDOC) and establishing sequential redox conditions in the subsurface resulted in enhanced removal of compounds with redox-dependent removal behavior such as trace organic chemicals. The aim of this study is to advance this concept from laboratory to full-scale application by introducing sequential managed aquifer recha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 47 publications
1
32
1
Order By: Relevance
“…Wiese et al [32] confirmed degradation under oxic conditions for diclofenac of >90%, whereas Rauch-Williams et al [18] reported a faster removal under anoxic conditions. Our findings are in accordance to Regnery et al [20], who proposed no complete removal of diclofenac during a short riverbank filtration but a rapid transformation in the second filtration step after reaeration.…”
Section: Torc Removal During Smartsupporting
confidence: 82%
See 2 more Smart Citations
“…Wiese et al [32] confirmed degradation under oxic conditions for diclofenac of >90%, whereas Rauch-Williams et al [18] reported a faster removal under anoxic conditions. Our findings are in accordance to Regnery et al [20], who proposed no complete removal of diclofenac during a short riverbank filtration but a rapid transformation in the second filtration step after reaeration.…”
Section: Torc Removal During Smartsupporting
confidence: 82%
“…After re-aeration of the extracted water, carbon-depleted and oxic conditions can be maintained in the subsequent subsurface filtration system. This approach was successfully demonstrated at the full-scale MAR facility Prairie Waters Project (Aurora, CO, USA) showing enhanced biodegradation of various TOrCs (e.g., caffeine, diclofenac, dilantin, gemfibrozil, meprobamate, and naproxen) compared to single-stage conventional riverbank filtration [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned, that artificial recharge of aquifers of the insufficient quality of pumped water may lead to increase the mobilisation of different pollutants in the unsaturated zone and reduce groundwater quality [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…The Italian project WARBO aims at facilitating the artificial recharge regulation in Italy by testing its application to mitigate the groundwater level drop in the Mereto site where the unused surplus surface water, which is usually lost during the winter-spring season, is utilized [2]. These area of research are very popular in different parts of the world, such as in Russia, Australia, Europe [2][3][4], Asia [1,[5][6][7][8], America [9,10] etc. [11,12].…”
Section: Introductionmentioning
confidence: 99%